2021
DOI: 10.3390/w13091180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplement Irrigation and Nitrogen Application Levels on Soil Carbon–Nitrogen Content and Yield of One-Year Double Cropping Maize in Subtropical Region

Abstract: Inappropriate irrigation conditions and nitrogen application can negatively affect soil carbon–nitrogen content and yield of maize, as well as can lead to underground water pollution and soil degradation. A two year (2018, 2019) field experiment was carried out to determine the effect of irrigation and N, alone and in combination on maize grain yield, grain nitrogen content, soil inorganic N and MBC of one-year double cropping maize (Zea mays L.) in a subtropical region. Split plot design was adopted, with mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…The research of Arora and Bhatla [ 60 ] revealed that melatonin directly modulates the activity of NR, GS, GDH, and GOGAT in response to abiotic stress conditions. The increased activities of these enzymes were related to melatonin, which enhanced the antioxidant properties of GS and GOGAT [ 18 ]. In this study, we found that melatonin with KNO 3 enhanced enzyme activity and accelerated the nitrogen metabolism in maize seedlings under waterlogging stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Arora and Bhatla [ 60 ] revealed that melatonin directly modulates the activity of NR, GS, GDH, and GOGAT in response to abiotic stress conditions. The increased activities of these enzymes were related to melatonin, which enhanced the antioxidant properties of GS and GOGAT [ 18 ]. In this study, we found that melatonin with KNO 3 enhanced enzyme activity and accelerated the nitrogen metabolism in maize seedlings under waterlogging stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fertilizer application rates have recently increased significantly in Chinese intensive agricultural systems, mostly for crop production. Higher N fertilizer input increased crop yield, but it also reduced plant N usage efficiency, and excess N can have major environmental and human health repercussions [ 18 ]. As a result, maintaining crop growth and production while lowering nitrogen fertilizer ratios poses a significant challenge to agriculture for long-term survival [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N) is the major source and a vital nutrient for plant growth and development because it affects the composition of proteins, nucleic acids, hormones, and other critical compounds [ 12 , 13 ]. To meet the agricultural demands of a growing population, synthetic N fertilizer application has increased dramatically in the last 50 years [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the losses of N with high irrigation water as a result of leaching may need more fertilization. Furthermore, these changes in bacterial diversity could be explained by the quality and amount of irrigation water and root exudates (Sawicka et al, 2020;Wang et al, 2021c), which are the most important sources of nutrients for rhizosphere bacteria. Primary metabolites including amino acids, carbohydrates, and organic acids (Hou et al, 2020), secreted by the plants roots have a positive effect on C and N concentrations, as well microbial population (Frenk et al, 2015(Frenk et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%